?âKARAGENAN TERMODIFIKASI POLIETILENIMINA DAN GLUTARALDEHID YANG DIOPTIMASI MENGGUNAKAN RESPONSE SURFACE METHODOLOGY (RSM) UNTUK ADSORPSI ION KROMIUM (VI) - Sibarani, Juliana
Chromium(VI) is one of the most commonly used heavy metal ions among other hazardous heavy metal ion. Chromium is widely used in the metallurgy, paint, electroplating and leather tanning industries. Chromium(VI) is highly toxic even at low concentrations. Chromium(VI) can damage water andsoil ecosystems and disrupt the metabolism of plants, animals and humans. In humans, repeated or prolonged exposure can damage the liver and diaphragm and cause irritation of the eyes and skin. Adsorption processes are widely used technologies for removing hazardous contaminants from wastewater due to their many advantages, including simplicity, ease of conditioning, high effectiveness, low cost, and environmental friendliness. Polymer based adsorbents are materials that have been extensively developed because of their high adsorption capacity. One such polymer that has been extensively developed is polyethyleneimine (PEI). PEI contains many amine groups, including primary, secondary, and tertiary amines. The presence of these amine groups contributes to the high adsorption capacity of PEI. However, PEI has a high solubility in water, so it must be immobilized on another matrix to be used as an adsorbent. A natural material that can be used as a matrix is ?-carrageenan. In this study, PEI was immobilized on ?-carrageenan using glutaraldehyde (GA) as a crosslinker. The adsorbent was prepared in the 0.5 x 0.5 x 0.5 cm cubes form using a simple and efficient technique. Response Surface Methodology (RSM) with Central Composite Design (CCD) was used for optimization during the adsorbent preparation stage. The PEI and GA compositions were independent variables, while the dependent variables optimized were adsorption capacity and swelling degree. The optimization results provided the optimal adsorbent composition was ?-carrageenan 2.5%, 1.11% PEI and 0.31% GA with and adsorption capacity 73.8 mg/g and swelling degree of 741%. The adsorbent is yellow in color and stable under acidic and basic conditions. The adsorbent was characterized using Fourier Transform Infrared (FTIR) and Scanning Electron Microscopy Energy Dispersive X-ray Spectroscopy (SEM EDS). The pHPZC of the adsorbent was determined using the floating method and a pHPZC of 10.19 was obtained. The study determined the optimum conditions for chromium(VI) adsorption, including pH, adsorbent dose, and contact time. In addition, kinetic adsorption studies, adsorption isotherms, and thermodynamics of adsorption were performed. The results showed that chromium(VI) adsorption with ?-carrageenan adsorbent modified with PEI and GA was optimal at pH 2, adsorbent mass of 0.075 g, and contact time of 3 h. Kinetic studies indicated that adsorption followed pseudo second order kinetics with a rate constant of 0.97×10–3 g/mg min. Adsorption followed the linear Langmuir isotherm model with a maximum adsorption capacity of 243.9 mg/g and a KL of 0.01499 L/mg. Based on thermodynamic studies, the ?G values at 303, 313, and 323 K were –31.23, –31.54, and –31.85 kJ/mol, respectively; ?H was –21.82 kJ/mol, and ?S was –0.03 kJ/mol K. This indicates that the chromium(VI) adsorption reaction by the ?-carrageenan adsorbent modified with PEI and GA is spontaneous and exothermic. The reusability of the ?-carrageenan adsorbent modified with PEI and GA was tested by performing repeated adsorption and desorption processes. Desorption was carried out using 0.1 M HNO3. The tests showed that the adsorbent can be reused up to 4 cycles